2019
DOI: 10.1111/zph.12627
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and prevention of tickborne diseases among Hispanic and non‐Hispanic residents of Maryland and Virginia

Abstract: Tickborne diseases (TBDs) such as Lyme disease (LD), babesiosis, ehrlichiosis and Rocky Mountain spotted fever cause substantial morbidity and even mortality in the USA. Data indicate that Hispanic populations may be at greater risk for occupational exposure to ticks and disseminated LD; however, information on knowledge and practices of Hispanic populations regarding TBDs is limited. We surveyed 153 Hispanic and 153 non‐Hispanic residents of Maryland and Virginia to assess awareness of TBDs, prevention practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Global warming, deforestation, and changes in precipitation [ 21 ], as well as other environmental conditions (habitat, climate, and dust and gas pollution) prevailing within urban heat islands have probably exerted an impact on tick abundance and activity, thus increasing the prevalence of LD over extensive areas [ 22 ]. Vegetation type and distribution (canopy, understory, and ground cover), human behavior [ 23 ], and seasons [ 24 ] have been found to be associated with an increased risk of tick bites [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global warming, deforestation, and changes in precipitation [ 21 ], as well as other environmental conditions (habitat, climate, and dust and gas pollution) prevailing within urban heat islands have probably exerted an impact on tick abundance and activity, thus increasing the prevalence of LD over extensive areas [ 22 ]. Vegetation type and distribution (canopy, understory, and ground cover), human behavior [ 23 ], and seasons [ 24 ] have been found to be associated with an increased risk of tick bites [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to inhand resources, a smartphone app has the potential to build community and engage hard-to-reach information seekers in a bidirectional manner (Cardona, 2013). In particular, lack of tick-borne disease awareness and language barriers have been identified as contributing factors in the under-and delayed diagnosis of Lyme disease among Spanish-speaking populations in the United States (Beck et al, 2022;Hu et al, 2019;Maxwell et al, 2022). A future direction of The Tick App would be to make the platform available in additional languages, starting with Spanish.…”
Section: Discussionmentioning
confidence: 99%
“…In nationwide cross-sectional surveys of tickborne disease attitudes and behaviours among the U.S. public from 2013 to 2015 (herein referred to as ConsumerStyles), 20.6% of respondents wore repellent, 15.5% showered after coming indoors and 19.4% checked for ticks daily . Results from a 2015 survey of Hispanic adults from outpatient clinics and community centres in Maryland and Virginia indicated that 36% of respondents wore repellent, 36% showered after coming indoors and 17% checked for ticks daily (Hu et al, 2019). The corresponding rates observed in our study were 29%, 11% and 12%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hispanic respondents were also less likely to report daily tick checks but were more likely to report showering soon after coming indoors to prevent tick bites. Adjusting for ethnicity and demographic variables, survey participants who primarily spoke Spanish were less likely to correctly identify the route of LD transmission, recognize LD symptoms and perform daily tick checks compared to those who primarily spoke English (Hu et al, 2019).…”
mentioning
confidence: 96%